The effect of the interactive small group study method on democratic attitudes and self-expression ability - Taspinar, Mehmet (Soc Personality Res Inc, 2006)
This study compared the Interactive Small Group Study Method (ISGS) with the Traditional Small Group Study Method (TSGS) from the viewpoint of the student's democratic attitude in the classroom and self-expression ability. Students at Firat University, Turkey, were divided into an experimental group and a control group each consisting of 30 members. ISGS was applied to the experimental group, TSGS was applied to the control group. The Democratic Attitude Related to Classroom Climate and Self-Expression Ability Scale (AS; Taspinar, 2001) was given pretest and posttest to both groups. Results showed a significant difference between the pretest and posttest scores of the two groups. The experimental group had a more positive attitude than the control group in the subdivision Presentation according to posttest scores. There was no significant difference for the other subdivisions. The ISGS method was found to be more effective than the CSGS method for both democratic attitudes and self-expression ability.
Keywords: group study; self-expression; teaching methods; teacher education; democratic attitudes